Rapid method for detecting thermostable nuclease in staphylococci - Růzicková, V (Folia microbiologica, 1991)
A rapid test for the detection of staphylococcal thermostable nuclease (TNase) is described. The procedure consists of heat inactivation of solid cultures of staphylococci and microslide agar diffusion in toluidine blue agar containing deoxyribonucleic acid. Using this method the results are obtained about 1 d sooner than with the conventional method.
Keywords: bakteriologické techniky; Bacteriological Techniques; Hot Temperature; Time Factors; časové faktory; Evaluation Studies as Topic; Staphylococcus; hodnotící studie jako téma; kultivační média; vysoká teplota; Micrococcal Nuclease; mikrokoková nukleasa; Culture Media